2011
DOI: 10.1097/bpb.0b013e32834493df
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolidase activity and oxidative–antioxidative status in Legg–Calve–Perthes disease

Abstract: We aimed to find out that whether collagen turnover is altered in the context of Legg-Calve-Perthes disease (LCPD) by evaluating serum prolidase activity. We also investigated the correlation between collagen turnover and oxidative-antioxidative status in LCPD. Plasma prolidase activity, total oxidant status (TOS), total antioxidant capacity, and oxidative stress index (OSI) were determined for 39 patients with LCPD and 40 healthy controls. Serum prolidase activity, TOS, and OSI were higher, but TAC was lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Although prolidase activity is found in a wide variety of diseases, reports have been contradictory. Several studies have reported that prolidase activity decreases in diseases such as osteoarthritis, 5 uraemic bone disease, 6 and osteogenesis imperfecta, 7 while increased prolidase activity has been described in Legg-Calve-Perthes disease 8 and idiopathic clubfoot. 4 In the current study, the increased serum prolidase levels in patients with DDH compared to controls may be a marker of increased collagen turnover and may be responsible for the altered histological structure of the joint capsule and other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although prolidase activity is found in a wide variety of diseases, reports have been contradictory. Several studies have reported that prolidase activity decreases in diseases such as osteoarthritis, 5 uraemic bone disease, 6 and osteogenesis imperfecta, 7 while increased prolidase activity has been described in Legg-Calve-Perthes disease 8 and idiopathic clubfoot. 4 In the current study, the increased serum prolidase levels in patients with DDH compared to controls may be a marker of increased collagen turnover and may be responsible for the altered histological structure of the joint capsule and other soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9,28 In the current study, we evaluated oxidative/antioxidative status. With respect to an increase in oxidative stress, our findings concurred with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum prolidaz aktivitesi ile oksidatif durum ilişkisinin incelendiği birçok çalışmada, kollajen metabolizması-nın oksidatif stres durumuyla ilişkili olduğu ve bu iliş-kinin etiyopatogenezde ve/veya hastalığın ilerleyişinde etkili olabileceği düşünülmüştür. [12,13] Bu mantıkla dü-zenlenen bir çalışmada, serum prolidaz aktivitesinin ve oksidatif stresin idiyopatik PEV ile ilişkili olabileceği ileri sürülmüştür. Prolidaz aktivitesi ile oksidatif ve antioksidatif parametreler beraberce incelenmiştir.…”
Section: Hi̇stopatoloji̇k çAlişmalarunclassified